European Monetary Union reform preferences of French and German parliamentarians - Sebastian Blesse; Pierre C. Boyer; Friedrich Heinemann; Eckhard Janeba; Anasuya Raj (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2019)
We analyze data from an author-conducted survey of members of the French and German parliaments on European Monetary Union reform preferences. We consider three potential drivers of preferences: nationality, ideology, and personal characteristics. For European Monetary Union policies like Eurobonds, the Fiscal Compact and the European Central Bank asset purchase program we find a robust difference between parliamentarians of both countries if they belong to the same party family and controlling for individual characteristics. Based on our estimates, however, we predict agreement between German left-wingers and French conservatives even for ideological differences that are smaller than the current difference between the left and the right European party families. Our findings suggest that deeply-rooted national differences do not impose a prohibitive obstacle to a German-French parliamentary consensus on European Monetary Union policies.
Keywords: E60; E62; F15; H60; 330; Comparative politics; European Monetary Union reforms; elite survey; members of national; parliament; policy preferences